Professional Commitment And Locus Of Control Toward Intensity In Whistleblowing Through Ethical Sensitivity - Muhammad Su’un; Hajering Hajering; Muslim Muslim (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2020)
: This study aims to examine the effect of professional commitment and locus of control on the intensity of conducting whistleblowing through ethical sensitivity. The data in this study were obtained from 4 public accounting firms in Makassar. This study uses primary data by conducting direct research in the field that provides questionnaires to 31 respondents and to test hypotheses using PLS (partial least square). The results found that partially professional commitment and locus of control had a positive relationship and had a significant effect on ethical sensitivity. Professional commitment and ethical sensitivity have a positive relationship with the intensity of whistleblowing. While the locus of control has a negative relationship, ethical sensitivity has a significant effect while professional commitment and locus of control have no significant effect. While the intervening variable partially shows that professional commitment and locus of control have a positive relationship and significantly influence the intensity of whistleblowing through ethical sensitivity.